Citra Destinasi dan Persepsi Harga Sebagai Prediktor Kepuasan Wisatawan - Afifah Sheila Ivanka; Nova Eviana (LPPM and Travel Operation Department Universitas Asa Indonesia, 2024)
This study explores the effect of destination image and perceived price on tourist satisfaction at Wiladatika Recreation Park. Adopting a descriptive quantitative approach, data were gathered through questionnaires administered to 100 purposively selected respondents who had previously visited the park. The collected data were then analyzed using multiple regression analysis. The findings revealed that both destination image and price perception partially and simultaneously affected tourist satisfaction at the park.